2018
DOI: 10.1016/j.autrev.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of ophthalmic imaging in central nervous system degeneration in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disorder that can involve any organ system. Central nervous system involvement can be a severe life threatening complication, ultimately resulting in severe neurodegenerative changes. Magnetic resonance imaging suggests that neurodegeneration, which may have deleterious effects on brain function, may occur early in SLE and experimental models suggest that neuroprotection may be feasible and beneficial. The retina is an extension of the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
(104 reference statements)
0
14
0
3
Order By: Relevance
“…Lupus retinopathy is a potentially sight-threatening complication that may manifest as retinal microangiopathy, retinal vasculitis or severe arterial or venous vaso-occlusion. 2 Lupus choroidopathy is another sight-threatening manifestation that can occur in isolation or associated with lupus retinopathy. It may present with single or multiple areas of serous retinal detachment, retinal pigment epitheliopathy, retinal pigment epithelium (RPE) detachment, choroidal ischemia or effusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lupus retinopathy is a potentially sight-threatening complication that may manifest as retinal microangiopathy, retinal vasculitis or severe arterial or venous vaso-occlusion. 2 Lupus choroidopathy is another sight-threatening manifestation that can occur in isolation or associated with lupus retinopathy. It may present with single or multiple areas of serous retinal detachment, retinal pigment epitheliopathy, retinal pigment epithelium (RPE) detachment, choroidal ischemia or effusion.…”
Section: Discussionmentioning
confidence: 99%
“…1 Posterior segment involvement, namely lupus retinopathy, choroidopathy and optic neuropathy is particularly concerning given their potential for a devastating impact on visual prognosis and their relation with poor systemic disease control. 2 According to most reports, lupus retinopathy is the second most common ocular manifestation with an incidence that may reach 29%. 3 However, over the last few years we have been entering a new era in the treatment of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…NPSLE is a severe complication of SLE, which results in severe neurodegenerative changes and threatens life [58]. NPSLE is characterized by a variety of neurological manifestations, making the diagnosis of NPSLE a formidable challenge for rheumatologists [59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology studies of the choroid in SLE patients have demonstrated mononuclear inflammatory cells within the choroid, reflecting choroidal vasculitis as well as immunoglobulin and complement deposition in the choroidal vasculature. 6,36 Consequently, choroidal blood supply is compromised, leading to choroidal thinning. Chronic ischemia induces long-term atrophy of choroidal stromal, which also leads to choroidal thinning.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the eye, SLE can affect almost any structure, including the vascular supply of the retina, the choroid and the optic nerve head. 6 Lupus choroidopathy is rare and can present with serous retinal detachment, retinal pigment epithelium detachment, retinal pigment epitheliopathy, choroidal ischemia or effusion. 5 When present, lupus choroidopathy is usually a marker of high disease activity and often associated with the central nervous system and renal disease.…”
Section: Introductionmentioning
confidence: 99%